Laparoscopic versus open appendicectomy: a non-randomized comparative study - Hanspal, Swatej; Shah, M. Yunus; Akhtar, Murtaza (International Surgery Journal, 2020)
Background: Appendicectomy is one of the most common surgical procedures performed in emergency surgery. Despite this, there is still lack of consensus about the most appropriate technique for appendicectomy. In this longitudinal analysis, we aimed to compare the outcomes of laparoscopic appendicectomy (LA) and the conventional technique or open appendicectomy (OA) in the treatment of acute appendicitis. Methods: A non-randomized longitudinal comparative study was conducted in NKP Salve Institute of Medical Sciences and Lata Mangeshkar Hospital, Nagpur, India. From November 2017 to October 2019, 53 patients underwent OA and 59 underwent LA, making a total number of patients included in this study to be 112 (n). The two groups were compared for operative time, length of hospital stay, postoperative pain, post-operative ileus and complication rate. Results: Laparoscopic appendicectomy was associated with a shorter hospital stay (4.34±1.37 days in LA and 5.09±1.71 days in OA, p<0.01), with a lower post operative pain score [VAS] (2.93±0.80 in LA and 4.62±0.92 in OA, p<0.001). Operative time was shorter in the open group (42.70±12.05 min in OA and 43.39±16.59 in LA). Complications were lesser in the LA group with a significantly lower incidence of wound infection (3.4% in LA and 13.2% in OA). Conclusions: Laparoscopic approach is safe and efficient in appendicectomy and it provides clinically advantages over open method (shorter hospital stays, lower post op pain, early food tolerance, earlier return to work and lesser wound infection) against only marginally longer operative time.